Solusi Pelaksanaan Bimbingan dan Konseling dalam Implementasi Kurikulum 2013 - Lattu, Desje (Guidance and Counseling Study Program, Pattimura University, 2017)
This research aims to: 1) To understand further the need for the implementation of counseling guidance in schools, 2) To find out the obstacles faced in the implementation of counseling guidance in schools, 3) Looking for solutions for the implementation of counseling guidance in schools in the implementation of the curriculum 2013. Benefits: 1) Provide real meaning to the school about the importance of counseling guidance in schools, 2) Overcoming the obstacles that arise in the implementation of counseling guidance in the implementation of curriculum 2013. This article was prepared using literature and interview methods. BK Implementation Solutions in the implementation of the 2013 curriculum: 1) Enlightenment about the role and role of BK to the school principal as the highest authority in the school in order to avoid BK dysfunction; 2) There is a need for continuous training of all BK teachers on how to implement BK in the implementation of the 2013 curriculum; 3) There is a need to study the theme relation and sub theme of BK material with related subjects so that although there is no time for BK material counseling but can be integrated in subject matter of certain subjects; 4) Guidance and Counseling Study Program as a teacher-producing institution BK needs to undertake a continuous assessment of the performance of BK teachers as alumni.